Pengaruh Adversity Quotient, Efikasi Diri, dan Self-Regulated Learning terhadap Prestasi Siswa SMA Islam Terpadu - Lenggono, Budi; Prabawanti, Ciptasari; Mujidin, Mujidin (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Full day school with a curriculum that integrates Islamic values has a solid activity. The purpose of this study was to determine the effect of adversity quotient (AQ), self-efficacy, and self-regulated learning on the learning achievement. This research was conducted at the Nur Hidayah Integrated Islamic High School, Sukoharjo. The subjects of this study were 102 students of class XI MIPA from a population of 195 people. The research sample was taken using simple random sampling technique. Data collection used the AQ scale, self-efficacy scale, self-regulated learning scale, and secondary data in the form of report card value data documents issued by schools. The data of this research were analyzed using linear regression analysis techniques which began with the assumption test including normality test, linearity test, multicollinearity test, and heteroscedasticity test. The results showed that as many as four proposed hypotheses were accepted. First, there is a significant effect between AQ, self-efficacy, and self-regulated learning simultaneously on learning achievement. Second, there is a significant effect of AQ on student learning achievement. Third, there is a significant effect of self-efficacy on learning achievement. Fourth, there is a significant effect of self-regulated learning on learning achievement.